The tropical cookbook: Termite diet and phylogenetics—Over geographical origin—Drive the microbiome and functional genetic structure of nests - González Plaza, Juan José; Hradecký, Jaromír (Frontiers in Microbiology, 2023)
Termites are key decomposers of dead plant material involved in the organic matter recycling process in warm terrestrial ecosystems. Due to their prominent role as urban pests of timber, research efforts have been directed toward biocontrol strategies aimed to use pathogens in their nest. However, one of the most fascinating aspects of termites is their defense strategies that prevent the growth of detrimental microbiological strains in their nests. One of the controlling factors is the nest allied microbiome. Understanding how allied microbial strains protect termites from pathogen load could provide us with an enhanced repertoire for fighting antimicrobial-resistant strains or mining for genes for bioremediation purposes. However, a necessary first step is to characterize these microbial communities. To gain a deeper understanding of the termite nest microbiome, we used a multi-omics approach for dissecting the nest microbiome in a wide range of termite species. These cover several feeding habits and three geographical locations on two tropical sides of the Atlantic Ocean known to host hyper-diverse communities. Our experimental approach included untargeted volatile metabolomics, targeted evaluation of volatile naphthalene, a taxonomical profile for bacteria and fungi through amplicon sequencing, and further diving into the genetic repertoire through a metagenomic sequencing approach. Naphthalene was present in species belonging to the genera Nasutitermes and Cubitermes. We investigated the apparent differences in terms of bacterial community structure and discovered that feeding habits and phylogenetic relatedness had a greater influence than geographical location. The phylogenetic relatedness among nests' hosts influences primarily bacterial communities, while diet influences fungi. Finally, our metagenomic analysis revealed that the gene content provided both soil-feeding genera with similar functional profiles, while the wood-feeding genus showed a different one. Our results indicate that the nest functional profile is largely influenced by diet and phylogenetic relatedness, irrespective of geographical location.